Effectiveness of flipped classroom for teaching anatomy and students' perceptions - S Viveka; T Vijay Sagar; M J Sudha (Wolters Kluwer Medknow Publications, 2017)
Background and objectives: A flipped classroom concept involves inverting the classroom teaching activities. Here, the learner learns the 'core' concepts before the class, usually at home, reading and watching an online video, at his will. The aim of current study was to evaluate the effectiveness of flipped classroom for teaching concepts in anatomy. The subject chosen was cranial nerves. Methodology: Ninety-two students participated in this study. Four topics from cranial nerves were selected for the project. Regular lecture classes were taken for first two topics. Flipped classroom was used for the next two. Videos intended for flipped classroom were made available to all students through WhatsApp platform and blog post 48 hours prior to class. Assessment was by MCQs - 25 from topics covered by conventional method and 25 from flipped classroom topics. Score of 50% was considered as pass. Number of students in pass and fail category were compared through chi- square test. Results: Mean scores after regular and flipped classes were 12.92 (SD ± 3.13) and 13.41 (SD ± 3.38) respectively. Fifty eight students passed after flipped classroom teaching and 47 students passed after regular class. The number of students passing after flipped class as compared to regular class is statistically significant. Perceptive rating of flipped classroom concept was 4.15 out of 5 in comparison to traditional methods. Conclusion: Flipped classroom is effective in learning anatomy. Studies pursued for longer duration with broader subject coverage are suggested.